Nordic collaboration in mathematics education research - Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2009)
The funding of the Nordic Graduate School in Mathematics Education (NoGSME) has come to an end but the Nordic collaboration continues ...